Studi Fenomenologi Tentang Pengalaman Pasien Hipertensi Terhadap Perawatan Dirinya Di Wilayah Kerja Puskesmas Andalas Padang Tahun 2017: Phenomenological Study of Hypertension Patient Experience Toward Self-care in the Andalas Padang Health Center Working Area in 2017 - Elvi Oktarina; Hayatunnupus Haqiqi; Esi Afrianti (NERS Jurnal Keperawatan, 2018)
Uncontrolled hypertension causes heart attacks, Cardiomegali, Heart Failure, Stroke, Kidney Failure, Blindness, and Cognitive Impairment. It requires proper strategy to maintain blood pressure in patients with hypertension called self management which consist of medication compliance, normal weight maintanance, low sodium consumption, physical activity, alcohol restriction and smoking cessation.. This research aimed to explore a deep understanding about the experience of Hypertension patients in carrying out self management. This research used qualitative method with descriptive phenomenology. Four people are selected by puposive sampling technique. Technique of data collection in this research with in-depth interviews. The data finding of this research were analyzed using Collaizi's method. The finding of data analyze is found eight theme: (1) the response to the disease suffered high blood pressure (2) first experience of hypertension (3) controlling (4) to cope with drug (5) maintain the health of the body (6) dietary changes (7) not smoking and drinking alcohol(8 ) family support. In this research, This research sugested the healthcare provider to contribute to improve information and knowledge of hypertension patients related to self management such as light exercise activities at home, salt consumption controlling, dietary recommendation and dietary restriction.